Angelic Wisdom about Divine Providence - Swedenborg, Emanuel, 1688-1772; Wunsch, William F. (William Frederic), 1882-1969 (Salt Lake City, UT : Project Gutenberg, 2006)
"Angelic Wisdom about Divine Providence" by Emanuel Swedenborg is a theological treatise written in the 18th century. This work explores the principles of divine providence, examining how God's infinite love and wisdom govern human life and the universe. The text delves into complex spiritual themes, emphasizing the relationship between divine laws, human freedom, and the nature of good and evil. The opening of the book establishes the foundational concepts surrounding divine providence. Swedenborg discusses how divine providence is the governance of the Lord's love and wisdom, and he articulates the necessity of understanding both the spiritual and natural worlds in this realm. The author underscores that true understanding comes from aligning human will and thought with divine intentions, indicating the interplay between human freedom and divine guidance. This opening portion sets the stage for the subsequent exploration of various laws and principles that govern the divine-human relationship, inviting readers to engage with profound philosophical and spiritual inquiries. (This is an automatically generated summary.)
Release date is 2006-06-05
Produced by William J. Rotella
Keywords: Providence and government of God -- Christianity